Development of Augmented Reality-Based Learning Media for Solid Geometry for Elementary School Students - Saputra, Ricky Aditya; Alfarizi, Muhammad; Saputri, Fiqih Hana; Ferawati, Ferawati (Sinkron : jurnal dan penelitian teknik informatika, 2025)
AR-based media is expected to create a more interactive and engaging learning experience, enhance students’ understanding, and motivate them to learn independently and actively in the digital era. The data collection stages applied include testing, observations, and the distribution of questionnaires. The development of this learning media follows the MDLC model, which aims to design improvements to the existing system. The results of the blackbox testing, the "Bangun Ruang" application is proven to be valid and successfully used, with excellent results in the SUS test, where the Ease of Use score reached 86%, Efficiency 88%, Effectiveness 90%, and Satisfaction 87%. This indicates that the application has high levels of usability, efficiency, and effectiveness, while also providing a satisfying user experience. The application not only operates according to the designed specifications but also provides a positive user experience. Thus, it can be widely used, especially in educational environments, to help students understand geometric concepts in a more interactive and engaging way. Developers can continue maintaining and improving the application based on user feedback to ensure it remains optimal and aligned with users' needs in the future.